Human β-Defensin-3 is Associated With Platelet-Derived Extracellular Vesicles and is a Potential Contributor to Endothelial Dysfunction - Panigrahi, Soumya; Ghosh, Santosh K.; Ferrari, Brian; Wyrick, Jonathan M.; Podrez, Eugene A; Weinberg, Aaron; Sieg, Scott F. (Frontiers in Molecular Biosciences, 2022)
While platelets are the essential mediators of hemostasis, they are being increasingly recognized for their potential to contribute to host defenses. Here, using immunofluorescent microscopy, western blot, and ELISA, we found that human β-defensin 3 (hBD-3), an important antimicrobial peptide produced by epithelial cells, can be detected in human platelets and megakaryocytes. Flow cytometry and immuno-electron microscopy revealed hBD-3 on the surface of thrombin-activated platelets. Moreover, hBD-3 was also found in platelet-derived exosomes (p-EVs), isolated from platelet-poor plasma and from platelet supernatants following thrombin stimulation. Incubation of platelets with hBD-3 peptide resulted in modest platelet activation and pre-incubation of platelets with synthetic hBD-3 prior to exposure to thrombin appeared to increase hBD-3 content in platelet lysates as well as in p-EVs, suggesting that hBD-3 can be initially taken up by platelets, perhaps via their open canalicular system. Interestingly, in vitro exposure of primary human endothelial cells to either hBD-3 peptide or purified p-EVs, caused significant endothelial dysfunction as documented by diminished levels of endothelial nitric oxide synthase (eNOS), Krüppel like factor-2 (KLF-2), and elevated relative expression of von Willebrand Factor (vWF). Pre-incubation of platelets with hBD-3 appeared to augment endothelial dysfunction caused by p-EVs. Overall, the current study provides evidence that hBD-3 enriched exosomes can be released by activated platelets and may play a role in positive feedback of platelet activation as well as in endothelial dysfunction. Theoretically, these effects could contribute to both cellular recruitment to the endothelium creating a pro-thrombotic vascular microenvironment that serves as a bridge between innate immunity and hemostasis.